Exploring the Silent Struggles of Gifted Adolescents in School Counseling Programs - Putra, Anak Agung Ngurah Adhi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the personal experiences of talented adolescents in facing often-overlooked challenges and examines the role of school counseling programs in addressing their needs. Using a phenomenological qualitative approach, the research involved 15 gifted students aged 13–17 enrolled in academic enrichment programs at three secondary schools, along with 3 school counselors as supporting informants. Data were collected through semi-structured in-depth interviews and participatory observations, then analyzed using NVivo-assisted thematic analysis. The findings reveal three key themes: excessive academic pressure and anxiety, difficulties in building peer relationships, and limitations of counseling programs that emphasize learning issues over psychosocial needs. Additionally, communication gaps among students, teachers, and counselors were identified, contributing to feelings of isolation. The study concludes that counseling programs should adopt a holistic approach integrating academic, social, and emotional support. Theoretically, it enriches understanding of the psychosocial dynamics of gifted adolescents, while practically offering recommendations for more adaptive and inclusive policies and counseling services.